Perspectives on Management of Dural Venous Sinus Thrombosis - Parry, Nicola (MD Conference Express, 2014)
Thrombosis of the dural venous sinus and/or cerebral veins (CVT) is a very complex problem that remains somewhat poorly understood. Yet, although it is an important consideration in cases of stroke, the evidence base for its medical and interventional management is lacking. This article discusses current perspectives on the pathogenesis and risk factors for CVT development, as well as treatment options. Other topics include the epidemiology and risk factors for CVT, medical management of CVT, as well as appropriate use of acute endovascular intervention.